Strongly perturbed state-selective charge exchange between slow Ar^{8+} and He - R. T. Zhang; J. W. Gao; Y. W. Zhang; D. L. Guo; Y. Gao; X. L. Zhu; J. W. Xu; D. M. Zhao; S. Yan; S. Xu; S. F. Zhang; Y. Wu; et al. (Physical Review Research, 2023)
We report an experimental and theoretical study of state-selective charge exchange processes in Ar^{8+} on He collisions at 1 and 3 keV/amu, benchmarking the fundamental electron capture dynamics under strong perturbations. The quantum-state selectivity has been experimentally resolved for one 1s electron of He capture into 4s, 4p, 4d+4f, and 5s states of Ar^{7+} ion along with the corresponding scattering angle differential cross sections. By comparing to theoretical calculations with a two-active-electron semiclassical asymptotic-state close-coupling approach, we are able to verify the important role of electronic correlations during the collisions and that the impact parameter sensitive transition probability significantly mediates the state-selective specifics.